PENGARUH PENGGUNAAN MEDIA MISTERY BOX TERHADAP KETERAMPILAN MENULIS KARANGAN NARASI SISWA KELAS V UPT SPF SDN KIP BARA-BARAYA I - Besse Riska Amalia; Tasrif Akib, Besse Syukroni (STKIP Subang, 2025)
The main problem in this study is how the use of mystery box media affects the writing skills of fifth grade students of UPT SPF SDN KIP Bara-Baraya I. The study aims to determine the effect of the use of mystery box media on the writing skills of fifth grade students of UPT SPF SDN KIP Bara-Baraya I. This type of research is experimental research (pre-experimental design) with a one-group pretest-posttest design. The sample used was 16 fifth grade students of UPT SPF SDN KIP Bara- Baraya I. The results showed that the average (mean) pretest value was 53.75 compared to the posttest value, which increased by 83.44. The results of the paired sample t-test showed that the sig. (2-tailed) obtained 0.001 which shows that 0.001 < 0.05 Based on the results obtained, it can be concluded that Ho is rejected and H1 is accepted which states that there is an influence of mystery box media on the narrative writing skills of class V students at UPT SPF SDN KIP Bara-Baraya I